JAL?L AD-D?N RUMI’S METHODS OF TEACHING (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The article deals with spiritual and moral upbringing of a person using the teaching methods of JalÄl ad-dÄ«n Rumi . The problems as relying on systematicity in the process of educating a person, coherence of information, correct setting of a pedagogical requirement, organization of an information through words and conversation, formation and reinforcement of a material by means of question and answer are analyzed from pedagogical point of view. The teachings of Rumi deal with the development of a person, his perfection and the realization of his self essence. His views reflect that coherence of the information in education is the foundation of conveying the information clearly, completely, compactly and relying on certain requirements. The poet emphasises the possibility of reaching one's goals by giving the demand an important role, he shows bilateral demand in the organization of the education and he himself brings up his students by frequently organizing colloquys with them. Rumi deeply understands the essence of the word and reaches the soul of his reader by the power ofword. Moreover, the ways and means of using Rumis ideas in the process of upbringing a perfect generation are indicated in this article. Key words: sytematicity, coherence, demand, colloquy, word, question and answer.